Tindak Tutur Komisif dalam Interaksi Jual Beli di Pasar Tradisional Karisa Kabupaten Jeneponto - Sri Rukmaeni Resa; Asia M; Sultan Sultan (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract.This study aims to describe the form of commissive speech acts in buying and selling interactions at Karisa Traditional Market, Jeneponto Regency and the function of commissive speech acts in buying and selling interactions at Karisa Traditional Market, Jeneponto Regency. The type and design of this research is descriptive qualitative. The data in this study are utterances or conversations between sellers and buyers during buying and selling interactions at clothing kiosks at Karisa Traditional Market, Jeneponto Regency. The techniques used are data collection techniques, data reduction, data presentation, and drawing conclusions. The object of this research is the speech between the seller and the buyer when they interact in buying and selling at the Karisa Traditional Market, Jeneponto Regency. The results of this study found two forms of commissive speech acts, namely direct and indirect speech acts. The direct speech acts consist of indirect speech acts in the form of news sentences (lampangana buritta), direct speech acts in the form of interrogative sentences (lampangana pakkutaknang), direct speech acts in the form of command sentences (lampangana parenta) and indirect speech acts. There are six functions of commissive speech acts, namely the function of promising (agreement), the function of offering (appakrara), the function of refusing (attollak), the function of guaranteeing (anjaming), the function of intending (akniak), the function of surrendering. The form and function of commissive speech acts used by sellers and buyers still need to be considered for errors in speech so that misunderstandings do not occur.Keywords: commissive speech act, speech, form, function, seller, buyer